Optimizing MSME Performance: The Impact of Accounting Bookkeeping, Cash Management, and Working Capital - Ni Kadek Marsya Maharani; Putu Riesty Masdiantini; Nyoman Suadnyana Pasek (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
The use of digital payment services with credit facilities, such as Shopee Paylater, has become increasingly popular among university students, potentially affecting their financial stability. This study aims to analyze the influence of financial literacy, financial behavior, and financial risk on the financial stability of active undergraduate Accounting students at Universitas Pendidikan Ganesha who use Shopee Paylater. This research employs a quantitative approach using a survey method and purposive sampling technique involving 100 respondents. Data were analyzed using multiple linear regression. The results indicate that financial literacy and financial behavior have a positive and significant effect on students’ financial stability, while financial risk has a negative and significant effect on financial stability. These findings emphasize that good financial literacy and sound financial behavior can promote the creation of financial stability among students, whereas a high level of financial risk tends to reduce that stability. This research is expected to serve as a reference for students in managing their finances wisely in the era of digital financial services.